Determinants of Capital Structure across Industries at Jakarta Stock Exchange - Christina Christina; Johan Halim (Journal of Applied Finance & Accounting, 2008)
There are several objectives to be accomplished in this study. The main purpose of this research is to determine the nature of capital structure across non-finance industries in Indonesia, whether they prefer to use debt or equity as their source of financing. Subsequently, factors that influenced the capital structure of a company are then identified. In this study, the company’s profitability, size, and dividend payout are considered as those factors that have relationship with leverage. Finally, this research also conducted to examine whether a company’s capital structure decision affects its growth of shares price. In doing so, multiple regression analysis is used in order to determine whether there is relationship between variables tested. The sample of analysis includes 230 companies listed in Jakarta Stock Exchange from all industries, except finance, in 2006. The findings of this research confirm that, first of all, capital structure varies across industries. Each industry would have different decisions regarding its optimal capital structure, depends on several factors. This leads to the second findings, in which it proves that there is negative significant relationship between profitability and leverage, positive significant relationship between company’s size and leverage, and negative relationship between dividend payout and leverage. Finally, this research also verifies that there is no relationship between leverage and company’s growth of shares price, which means that the growth of shares price is not influenced by the company’s capital structure decision. Capital structure decision plays an important role in maximizing the firm’s value. By having the most optimal capital structure, firms might be able to push its cost to the minimum point, which then assist them in dealing with the competitive environment. Consequently, it is important to determine the factors that influence the capital structure of companies.